Plan estratégico para potenciar y consolidar las habilidades de gestión microempresarial en la provincia de Pichincha - Garcés Ramos, Víctor Hugo (2007)
Knowing the conditions under which currently microenterprise it operates in the Province of Pichincha, by applying a survey of a representative sample of the microenterprise sector, to obtain data consistent with reality and thus be more accurate in the study and feasibility of our proposal.